2003
DOI: 10.1023/b:cyto.0000009820.72920.cf
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysate: a replacement for fetal bovine serum in animal cell culture?

Abstract: A new cell culture supplement, platelet lysate, was evaluated with reference to fetal bovine serum (FBS), an established industrial medium for animal cell culture. Chemical and bacteriological profiles were conducted including the presence of platelet-derived growth factor (PDGF). PDGF was detected in the platelet lysate but it was not present in FBS. The platelet lysate medium demonstrated lack of microorganisms, mycoplasma and endotoxins. The platelet lysate was investigated in culture studies (cell growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 9 publications
2
32
1
2
Order By: Relevance
“…Other laboratories have already suggested that platelet lysates are a valuable, non-xenogenic alternative to FBS in cell culture (Bernardo et al, 2007;Doucet et al, 2005;Johansson et al, 2003). Physiologically, activated platelets are known to deliver a broad spectrum of growth factors and other active molecules by exocytosis at the site of injury.…”
Section: Cell Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratories have already suggested that platelet lysates are a valuable, non-xenogenic alternative to FBS in cell culture (Bernardo et al, 2007;Doucet et al, 2005;Johansson et al, 2003). Physiologically, activated platelets are known to deliver a broad spectrum of growth factors and other active molecules by exocytosis at the site of injury.…”
Section: Cell Extractionmentioning
confidence: 99%
“…Since then a whole range of substitutes have become commercially available or are still under investigation, including chemically-defined media substitutes, tissue extracts (e.g., pituitary extracts), ocular fluid (Filipic et al, 2002), bovine milk fractions or bovine colostrum (Belford et al, 1995), plant extracts (vegetal serum) (Pazos et al, 2004), and platelet lysates (Johansson et al, 2003).…”
Section: Stimulation Of Erk1/2 Map Kinasesmentioning
confidence: 99%
“…One common supplement is serum collected from blood as it provides a broad spectrum of macromolecules, carrier proteins for lipoid substances, trace elements, attachment and spreading factors, low molecular weight nutrients, hormones and growth factors (Gstraunthaler 2003). Foetal bovine serum (FBS) is the most widely used supplement for in vitro culture media (Jayme and Blackman 1985;Liselott et al 2003). The collection of serum from bovine foetuses has been the issue of moral concerns (Jochems et al 2002;van der Valk et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…( BIAGGIO et al, 2015 apud VAN DER VALK et al, 2010) FILIPIC et al, 2002), frações de leite bovino ou colostro bovino (BELFORD et al, 1995), extratos de plantas (soro vegetal) (PAZOS et al, 2004) e lisados de plaquetas (JOHANSSON et al, 2003).…”
Section: Lista De Ilustraçõesunclassified
“…In conclusion, the cells cultured in SFM are able to grow in a manner similar to those grown with FBS, and are also capable of producing ppHCV-RVGP, with promising alternatives for the production of proteins and /or recombinant viruses. (JOHANSSON et al, 2003). …”
mentioning
confidence: 99%